Interpreting precipitation δ 18 O over eastern China for the Asian summer monsoon: Results from the last millennium simulations - Yujia Liu; Wenmin Man; Tianjun Zhou (International Journal of Climatology, 2023)
The Asian summer monsoon (ASM) plays a major role in the Asian climate system, affecting nearly half of the world's population. The oxygen isotopes of speleothem calcite (δ 18 O c ) records in China provide important insights into past ASM changes; however, it remains controversial whether the δ 18 O c records over eastern China (EC) mainly reflect the Indian summer monsoon (ISM) or East Asian summer monsoon (EASM). In this study, we estimate the relationships between precipitation‐weighted oxygen isotopes (δ 18 O pw ) and various ASM indices over the last millennium based on the isotope‐enabled Community Earth System Model. The δ 18 O pw in EC mainly characterizes the intensity of the ISM and, to some extent, reflects the meridional wind component of the EASM, but it has an opposite relationship with the zonal wind component of the EASM. Although the limitations of various EASM definitions lead to the contrary relations between the δ 18 O pw and EASM indices, the δ 18 O pw in EC is accompanied by consistent EASM footprints. Moreover, although the meridional wind‐based EASM indices are negatively correlated with δ 18 O pw over EC, the relationships are much weaker than that with the ISM indices. The widespread negative δ 18 O pw signals extending from the Indian Peninsula to East Asia are closely coupled with the low‐level circulation over the ISM region. When considering the relationship between the EASM and δ 18 O pw over EC, the positive contribution from the Northwest Pacific offset the negative contribution from the remote Indian Ocean, leading to the insignificant correlation between the EASM indices and δ 18 O pw over EC.